Find all functions $f:\mathbb{R} \rightarrow \mathbb{R}$ so that:

a) $[f(x)+f(y)][f(x+2y)+f(y)]=[f(x+y)]^2+f(2y)f(y)$

b) for every real $a>b\ge 0$ we have $f(a)>f(b)$

As much as I know:

  • putting $x=y=0$ we get $f(0)=0$.

  • let $x+y=0$, the we get $f(y)+f(-y)=\frac{f(2y)}{2}$


Step 1: Prove : $f(y) = 0$ iff. $y=0$

It's easy to see $f(y)>0$ for $y>0$ (from porperty (b) with value $a=y,b=0$)

Following proof is given by @Kyson

To prove that $f(y)≠0$ for all$ y<0.$

Assume there is a $y<0$ such that $f(y)=0.$

Choose $x=−2y>0$ and hence $f(x)>0$ and $f(x+y)=f(−y)>0 $Then $[f(x)+f(y)][f(x+2y)+f(y)]=0$ while $f(x+y)2+f(y)f(2y)>0.$

$ \ $

Step 2: Prove $f(y)$ is even.

Put $x+y=0$ in equation given to get:$f(y)+f(-y)=\frac{f(2y)}{2}$ for all y. $f(y)+f(-y)=\frac{f(2y)}{2} = f(-y) +f(y) = \frac{f(-2y)}{2} $ Thus $f(x) $is a even function, so $f(y)+f(-y)=2f(y)=\frac{f(2y)}{2} \Rightarrow f(2y)=4f(y) $ (Since $f(x)$ is even ,property (b) actually shows that $f(y) > 0$ on $(-\infty,0)\cup(0,\infty)$)

$ \ $

Step 3: Prove:$ f(y)=y^2f(1)$

By induction , find $f(ny)=n^2f(y)$ where $n \in \mathbb N$

Details of induction: Suppose $m\in \mathbb N ,m\ge 2 ,\ f(ny)=n^2f(y)$ holds for all $n\le m$
Put $x=(m-1)y$ in property (a).$\\ \Rightarrow ((m-1)^2+1)f(y)f((m+1)y)=(m^4+4-(m-1)^2-1)f^2(y) \\ \Rightarrow f((m+1)y)=(m+1)^2f(y) \ for\ y\not = 0 \ and \ it\ still\ holds\ for\ y=0$

Hint: $(m+1)^2 ((m-1)^2 +1) = (m^2-1)^2+(m+1)^2=m^4 -m^2+2 =m^4+4-(m-1)^2-1$

Remark: Result induces $f(zy)=z^2f(y)$ where $z\in \mathbb Z$ , since $f$ is even.

$ \ $

$\forall r\in \mathbb Q , \ r = \frac ab \ , \ a,b\in \mathbb Z$ . Then $f(ry)=f(\frac ab y)=a^2f(\frac 1b y)$ and $f(y)=b^2f(\frac 1b y)$

Hence $f(ry)=f(\frac ab y)=(\frac ab)^2f(y)=r^2f(y)\Rightarrow f(r)=r^2f(1)$

As @MarkBennet points out:

the function is strictly increasing for $r≥0$ and the rationals are dense in the reals.

And $f(r)$ is even, so it's strictly decreasing for $r\le 0$.

Conclude $f(x)=x^2f(1)$ where $x\in \mathbb R $

Thus $f(x)$ can only be the form such as $ax^2$ where $a\in \mathbb R^+$

  • $\begingroup$ You can get $f(r)=r^2f(1)$ for rationals, and then use the fact that the function is strictly increasing for $r\ge 0$ and the rationals are dense in the reals to conclude. But the final equation in the original post involves dividing by $f(y)$ and this could be zero for some negative $y$, in which case that equation need not hold (without more work). $\endgroup$ – Mark Bennet Jan 24 '15 at 15:10
  • $\begingroup$ @MarkBennet thank you! I will complete proof later. $\endgroup$ – Syuizen Jan 24 '15 at 15:15
  • $\begingroup$ Can you please show the induction part and why it also holds for rational beacuse it is a key part in solving the problem. $\endgroup$ – HeatTheIce Jan 24 '15 at 19:58
  • $\begingroup$ @SoulEater I edit my answer. Show all details of the proof and the ideas. $\endgroup$ – Syuizen Jan 25 '15 at 2:29

This may help to get you to the next step.

From the last equation, put $z=-y$ to obtain $\frac {f(-2z)}2=f(z)+f(-z)=\frac {f(2z)}2$. This means that generally $f(x)=f(-x)$ so that, again from the last equation, $f(2y)=4f(y)$.

  • $\begingroup$ Let $x+y=0$, we get $f(y)=0$ or $f(y)+f(-y)=\frac{f(2y)}{2}$. Since $f(y)>0$ for all $y>0$, we have $f(y)+f(-y)=\frac{f(2y)}{2}$ for all $y\ge0$. I wonder whether we can substitute $z=-y$. $\endgroup$ – velut luna Jan 24 '15 at 14:41
  • $\begingroup$ $f(x)=ax^2$, where a is a real parameter, is a solution. Maybe the only one. $\endgroup$ – HeatTheIce Jan 24 '15 at 14:45
  • $\begingroup$ @Kyson Yes, there is more work needed to establish the equation for $x+y=0$ because it may involve dividing through by zero if $f(y)=0$ for some $y\lt 0$. It holds when $f(y)\neq 0$ even if $y$ is negative. $\endgroup$ – Mark Bennet Jan 24 '15 at 15:00
  • $\begingroup$ It cant be zero bcs f is not a constant function (it is a strictly incrising one). $\endgroup$ – HeatTheIce Jan 24 '15 at 15:02
  • $\begingroup$ Putting $x=y$ you get $f(3x)=9f(x)$. $\endgroup$ – HeatTheIce Jan 24 '15 at 15:18

This may help Mark Bennet's proof a little bit.

To prove that $f(y)\ne0$ for all $y<0$.

Assume there is a $y<0$ such that $f(y)=0$.

Choose $x=-2y>0$ and hence $f(x)>0$ and $f(x+y)=f(-y)>0$

Then $[f(x)+f(y)][f(x+2y)+f(y)]=0$ while $f(x+y)^2+f(y)f(2y)>0$.

  • $\begingroup$ Nicely reasoned! $\endgroup$ – Mark Bennet Jan 24 '15 at 15:25

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.